2010
DOI: 10.1016/j.janxdis.2009.09.009
|View full text |Cite
|
Sign up to set email alerts
|

“I see what you’re saying”: Intrusive images from listening to a traumatic verbal report

Abstract: We tested the hypothesis that intrusive visual images could develop from listening to a traumatic verbal report. Eighty-six participants listened to a traumatic verbal report under one of three conditions: while shaping plasticine (visuospatial condition), while performing articulatory suppression (verbal condition), or with no extra task (control condition). Results showed that intrusive visual images developed from listening to the traumatic report. In line with the idea that central executive processes guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 35 publications
2
49
1
2
Order By: Relevance
“…Participants' hands were covered with a larger box so that visual attention to the film was maintained. A similar experimental procedure (Krans et al, 2010) has been shown to successfully interfere with cognitive processing when viewing a trauma film.…”
Section: Sensory/perceptual Interference Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants' hands were covered with a larger box so that visual attention to the film was maintained. A similar experimental procedure (Krans et al, 2010) has been shown to successfully interfere with cognitive processing when viewing a trauma film.…”
Section: Sensory/perceptual Interference Taskmentioning
confidence: 99%
“…Some studies have used the film paradigm to directly investigate whether inhibiting sensory/perceptual processing of the film by asking participants to perform a concurrent visuospatial task, such as key tapping or clay modelling, interferes with sensory/perceptual processing and decreases the frequency of intrusive memories (Bourne, Frasquilho, Roth, & Holmes, 2010;Holmes, Brewin & Hennessy, 2004;Krans, Näring, Holmes, & Becker, 2010;Stuart, Holmes, & Brewin, 2006). These studies have consistently found a significant reduction in the frequency of intrusive memories when participants perform a concurrent visuospatial task in comparison to a control condition with no assigned task.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported results in line with these hypotheses Bourne et al 2010 ) . However, others have reported that concurrent tasks from both modalities can reduce intrusion frequency (Krans et al 2009(Krans et al , 2010aPearson and Sawyer 2011 ; . Overall, fi ndings indicate that more sensory information will lead to more intrusive memories, but the role of verbal conceptual processing is still unclear.…”
Section: Theoretical Explanations Of Intrusive Memories In Ptsdmentioning
confidence: 98%
“…Interestingly, it has been noted in several survey studies that therapists working with PTSD patients can develop visual intrusive images of their patient's trauma narrative (McCann and Pearlman 1990 ;Arvay 2001 ) . In two controlled studies, student participants who were asked to listen to an actor-narrated "journalist report" of a traumatic traf fi c accident went on developing intrusive images of that event (Krans et al 2010a(Krans et al , 2011 . In response to hearing an account of the trauma they developed intrusive images that were strikingly similar to those reported by participants who actually watched a traf fi c accident fi lm.…”
Section: Intrusive Memories In Ptsdmentioning
confidence: 99%
“…begun to consider prospective imagery 'flash-forwards' (Engelhard, Van den Hout, Janssen, & Van der Beek, 2010;Morina, Deeprose, Pusowski, Schmid, & Holmes, 2011), and imagery with an entirely imaginary basis (Krans, Näring, Holmes, & Becker, 2010).…”
mentioning
confidence: 99%